Irregular precipitation events in control of seasonal variations in CO2 exchange in a cold desert-shrub ecosystem in northwest China. (September 2015) - Xie, Jing; Zha, Tianshan; Jia, Xin; Qian, Duo; Wu, Bin; Zhang, Yuqing; Bourque, Charles P.-A.; Chen, Jiquan; Sun, Ge; Peltola, Heli
Abstract: Net ecosystem productivity (NEP) of a cold desert-shrub ecosystem was continuously monitored during 2012 and 2013 using the eddy covariance method. The aim was to examine the influence of irregular precipitation in control of seasonal variations in NEP at multiple timescales. The ecosystem was a weak annual carbon sink. Difference in NEP between 2012 and 2013 (2013, having higher NEP) was caused by a suppression in gross ecosystem productivity (GEP; 55 g C m −2 ) compared to ecosystem respiration (ER; 33 g C m −2 ) in 2012, as a result of (i) fewer frequent and low-intensity rainy days and more carbon-source days in summer, (ii) lower annual mean air and soil temperature, and (iii) lower daily mean photosynthetically active radiation. Daily GEP and ER both decreased during dry periods, with GEP decreasing more than ER, causing NEP to decrease. Persistent and high available soil water associated with frequent and low-intensity precipitation during DOY 207 to 224 was central to maintaining carbon-sink strength in 2013, resulting in a noticeable increase in daily NEP from 0.3 g C m −2 to 1.2 g C m −2 . Frequent and low-intensity precipitation was responsible for maintaining plant growth, while sporadic and high-intensity precipitation decreased NEP. Highlights: Seasonal carbon cycle was established for a cold desert-shrub ecosystem. The ecosystem was a weak sink for CO2 on an annual basis. Frequent and low-intensity precipitation maintained carbon sink strength. Sporadic and high-intensity precipitation increased ER more than GEP.